Proptosis with Increased Orbital Fat in an Obese Patient - Azhar Seedat; Shaheen Seedat; Sulaiman E. I. Moosa (Case Reports in Radiology)
Computational tomography (CT) is a well-documented modality in the workup of proptosis. We present a case of proptosis due to increased orbital fat in an obese patient. We review the literature to discuss the most likely causes of increased orbital fat, and we discuss the utility of CT imaging in assessing this pathology.